Sustainable Surface Water Management 2016
DOI: 10.1002/9781118897690.ch7
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Drainage Systems

Abstract: (since 2010). He is also the Head of the Civil Engineering Research Group. About 47% and 44% of his research activities are in water resources management systems and wastewater treatment engineering systems, respectively. The remaining 9% are in capillary processes and water treatment systems. Prof. Scholz obtained his PhD from The University of Birmingham. He has shown individual excellence evidenced by world leading publications, postgraduate supervision and research impact. Miklas has published two books an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Second, during the process of soil erosion, soil is prevented from being swept or blown away by the plant roots that hold the soil in place and redesign the rhizosphere to alter the three−dimensional physical architecture and water dynamics as a physical barrier (Bashir et al, 2018;Rabbi et al, 2018), moreover, high root density can protect soil detachment and increase infiltration, thus reducing soil loss (Gyssels et al, 2005). Third, during the process of soil deposition and redistribution, the plants slow down water as it flows over the land, allowing much of the runoff to soak into the ground (Graham, 2017;Gachene et al, 2019).…”
Section: Mechanism Of Vegetation Effects On Soil and Nutrient Exportmentioning
confidence: 99%
“…Second, during the process of soil erosion, soil is prevented from being swept or blown away by the plant roots that hold the soil in place and redesign the rhizosphere to alter the three−dimensional physical architecture and water dynamics as a physical barrier (Bashir et al, 2018;Rabbi et al, 2018), moreover, high root density can protect soil detachment and increase infiltration, thus reducing soil loss (Gyssels et al, 2005). Third, during the process of soil deposition and redistribution, the plants slow down water as it flows over the land, allowing much of the runoff to soak into the ground (Graham, 2017;Gachene et al, 2019).…”
Section: Mechanism Of Vegetation Effects On Soil and Nutrient Exportmentioning
confidence: 99%
“…As pointed by Hellström et al [ 7 ], these techniques can clean wastewater to avoid unhygienic conditions for users and mitigate stormwater to prevent damage derived from flooding. Green SuDS have been recommended because of the increase in evapotranspiration they involve, which has a positive impact on microclimates in urban areas, a factor of great importance to the health of urban dwellers [ 8 , 9 ]. Charlesworth [ 10 ] showed that SuDS also involve multiple benefits in the context of Climate Change for human and environmental health by carbon sequestration and storage, mitigation of the urban heat island effect and urban cooling.…”
Section: Introductionmentioning
confidence: 99%
“…SUDS design should rely on the concept of 'management train', consisting of a sequence of SUDS techniques that aim to reduce flow rates and volumes and minimise pollution (Woods-Ballard et al, 2015;Graham, 2016). These techniques need to be gradually applied from prevention, source control, site control through to regional control.…”
Section: Storm Water Systemsmentioning
confidence: 99%
“…As examples of source control techniques, there are green roofs, permeable surfaces, bio retention areas, filter strips and local infiltration. The most common site control techniques are detention and retention basins, swales and urban ponds, and at a regional scale, retention ponds and wetlands are some of the options (Graham, 2016).…”
Section: Storm Water Systemsmentioning
confidence: 99%